The GPR120 Agonist TUG-891 Inhibits the Motility and Phagocytosis of Mouse Alveolar Macrophages. (22nd February 2020) - Su, Xing-Li; Liu, Ying-Guang; Shi, Man; Zhao, Yan-Yan; Liang, Xiang-Yan; Zhang, Li-Jun; Wei, Lan-Lan; Zhao, Yu-Feng
Abstract : Movement and phagocytosis characterize the fundamental actions of macrophages. Although it is known that the free fatty acid receptor GPR120 is expressed in macrophages and regulates cytokine expression to exert anti-inflammatory activities, the effects of GPR120 activation on the motility and phagocytosis of macrophages are not clear. In this study, mouse alveolar macrophages (AM) were stimulated with the GPR120 agonist TUG-891, and the changes in cell motility, intracellular Ca 2+ concentration ([Ca 2+ ]i), and the ability of phagocytosis were measured. Mouse AM in controls exhibited active movement in vitro, and TUG-891 significantly restrained AM movement. Meanwhile, TUG-891 stimulated a quick increase in [Ca 2+ ]i in AM, which was blocked separately by the Gq protein inhibitor YM-254890, the phospholipase C (PLC) inhibitor U73122, or depletion of endoplasmic reticulum (ER) Ca 2+ store by thapsigargin. The inhibition of AM movement by TUG-891 was eliminated by YM-254890, U73122, thapsigargin, and chelation of cytosolic Ca 2+ by BAPTA. Moreover, TUG-891 inhibited AM phagocytosis of fluorescent microspheres, which was also blocked by YM-254890, U73122, thapsigargin, and BAPTA. In conclusion, GPR120 activation in mouse AM increases [Ca 2+ ]i but inhibits the motility and phagocytosis via Gq protein/PLC-mediated Ca 2+ release from ER Ca 2+ store.